Heterologous Production of the Marine Myxobacterial Antibiotic Haliangicin and Its Unnatural Analogues Generated by Engineering of the Biochemical Pathway - Sun, Yuwei (Sci Rep, 2016)
Despite their fastidious nature, marine myxobacteria have considerable genetic potential to produce novel secondary metabolites. The marine myxobacterium Haliangium ochraceum SMP-2 produces the antifungal polyketide haliangicin (1), but its productivity is unsatisfactory. The biosynthetic gene cluster hli (47.8 kbp) associated with 1 was identified and heterologously expressed in Myxococcus xanthus to permit the production of 1 with high efficiency (tenfold greater amount and threefold faster in growth speed compared with the original producer), as well as the generation of bioactive unnatural analogues of 1 through gene manipulation. A unique acyl-CoA dehydrogenase was found to catalyse an unusual γ,δ-dehydrogenation of the diketide starter unit, leading to the formation of the terminal alkene moiety of 1. Biological evaluation of the analogues obtained through this study revealed that their bioactivities (anti-oomycete and cytotoxic activities) can be modified by manipulating the vinyl epoxide at the terminus opposite the β-methoxyacrylate pharmacophore.